Analysis of The High-Resolution Fourier Spectrum of The v6 Band of The Cis-C2H2D2 Molecule - Konov I. A.; Chertavskikh Yu. V. Yulia Vladimirovna; Fomchenko A. L. Anna Leonidovna; Aslapovskaya Yu. S. Yuliya Sergeevna; Zhdanovich S. A.; Sydow C. (2016, 2016)
Title screen